How Discharge Instructions Can Change a Life - Joseph M. Geskey (SLACK Incorporated, 2018)
Eight years ago my father was being released home from the large academic hospital where I worked, and I was able to be present for his discharge instructions. I was not wearing my white coat or hospital badge and, therefore, was treated as a layperson in this specialized unit because I didn't visit it routinely in my clinical practice. Table 1 is an approximation of the discharge summary my father received. It should be noted that my father was actually taking 25 mcg of fentanyl (not the 125-mcg dose he was erroneously going to be discharged on) to dull the pain and burning he felt in his mouth and throat from the chemotherapy and radiation he was receiving as part of his treatment regimen for stage III head and neck cancer. The combination of pain and loss of appetite led to the placement of a gastrostomy tube so that he could receive adequate nutrition, hydration, and prescription medications. There were several duplications of medications in different formulations, frequencies, and routes of administration, such as ciprofloxacin, prochlorperazine, and a prescription mouthwash. Also, the medical abbreviation "PO" and the more patient-friendly term "orally" were used interchangeably. When my father received these instructions he was asked if he had any questions, and as anyone who has been present when discharge instructions are given to a friend or family member can probably attest, he quickly answered, "No."